TICKS INFESTING SHEEP AND GOAT IN WESTERN UTTAR PRADESH - SHARMA, B.; KUMAR, D.; SHARMA, N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
In a survey of ticks infestation during 2003, four ixodids species were recorded infesting sheep and goats in three tehsils viz. Meerut City, Mawana and Sardana under district Meerut located in western belt of Uttar Pradesh. These species are named, Hyalomma anatolicum anatolicum, H. kumari, Ixodes granulatus and Rhipicephalus haemaphysaloides. The percentage of infestation of ticks was more in 3rd quarter of the year and was maximum in Tehsil Sardana.